2011
DOI: 10.1371/journal.ppat.1002338
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Transition to Pathogenicity in Chytrid Fungi

Abstract: Understanding the molecular mechanisms of pathogen emergence is central to mitigating the impacts of novel infectious disease agents. The chytrid fungus Batrachochytrium dendrobatidis (Bd) is an emerging pathogen of amphibians that has been implicated in amphibian declines worldwide. Bd is the only member of its clade known to attack vertebrates. However, little is known about the molecular determinants of - or evolutionary transition to - pathogenicity in Bd. Here we sequence the genome of Bd's closest known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
108
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(113 citation statements)
references
References 47 publications
4
108
1
Order By: Relevance
“…The inability of R. irregularis to grow in vitro suggests that the obligate biotroph genome may lack genes typically present in autotrophic fungi. Thus, we systematically searched for genes absent in R. irregularis, the obligate biotrophic pathogen Blumeria graminis (20), and early diverging Mucoromycotina and Chytridiomycota genomes (23) but present in the well-annotated yeast (Saccharomyces cerevisiae) genome (SI Appendix, Table S9). Genes encoding enzymes of primary metabolism are retained in R. irregularis [(Kyoto Encyclopedia of Genes and Genomes; KEGG) Metabolic Pathways database; jgi.doe.gov/Rhizophagus], but several key genes are missing in the genome assemblies of both the obligate biotrophs R. irregularis and B. graminis (see below), suggesting that the lack of these genes is an evolutionary adaptation to the obligate biotrophy.…”
Section: Resultsmentioning
confidence: 99%
“…The inability of R. irregularis to grow in vitro suggests that the obligate biotroph genome may lack genes typically present in autotrophic fungi. Thus, we systematically searched for genes absent in R. irregularis, the obligate biotrophic pathogen Blumeria graminis (20), and early diverging Mucoromycotina and Chytridiomycota genomes (23) but present in the well-annotated yeast (Saccharomyces cerevisiae) genome (SI Appendix, Table S9). Genes encoding enzymes of primary metabolism are retained in R. irregularis [(Kyoto Encyclopedia of Genes and Genomes; KEGG) Metabolic Pathways database; jgi.doe.gov/Rhizophagus], but several key genes are missing in the genome assemblies of both the obligate biotrophs R. irregularis and B. graminis (see below), suggesting that the lack of these genes is an evolutionary adaptation to the obligate biotrophy.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, as Berger et al (28) hypothesized in their seminal study discovering B. dendrobatidis, we postulated that B. dendrobatidis might be producing a factor that can cause pathology in the absence of actual infection; for instance, B. dendrobatidis produces proteolytic enzymes known to degrade host tissues (22,(29)(30)(31). To test this hypothesis, we exposed P. alleni to (i) an unfiltered B. dendrobatidis + inoculum, (ii) a B. dendrobatidis + inoculum where all of the zoospores and zoosporangia were removed with a 0.7 μm filter, or (iii) a control B. dendrobatidis − inoculum filtered through a 0.7 μm filter (n = 5 per treatment).…”
Section: Resultsmentioning
confidence: 95%
“…35 and 36). Whether these pathology-inducing chemicals released by B. dendrobatidis are known proteases (22,(29)(30)(31) and are the cause of B. dendrobatidis-induced electrolyte imbalance and cardiac arrest in amphibians (37) remains to be tested.…”
Section: Resultsmentioning
confidence: 99%
“…Because preliminary studies suggested that lymphotoxic activity could be detected in low-molecular-weight fractions derived from the B. dendrobatidis Sup, we used LC-MS with UV-Vis detection to investigate small molecules produced by the original type strain of B. dendrobatidis (isolate JEL197) (2) but not by the closely related nonpathogenic chytrid H. polyrhiza (15,17). The B. dendrobatidis Sup from cultures of maturing zoosporangia grown overnight in water (11) consisted of a mixture of two major lightabsorbing components as well as a number of less abundant components not present in the H. polyrhiza supernatant (Fig.…”
Section: B Dendrobatidis Metabolites and Their Lymphotoxic Activitymentioning
confidence: 99%